2019
DOI: 10.1128/msphere.00339-19
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Mouse Models of Disseminated Candida auris Infection

Abstract: Disseminated candidiasis is a life-threatening disease and remains the most common bloodstream infection in hospitalized patients in the United States. Despite the availability of modern antifungal therapy, crude mortality in the last decade has remained unacceptably high. In particular, Candida auris is a multidrug-resistant, health care-associated fungal pathogen and has recently emerged as the first fungal pathogen to cause a global public health threat. A reliable animal model for disseminated C. auris can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 31 publications
7
50
0
Order By: Relevance
“…Recent studies have documented the virulence of C. auris in murine models of invasive candidiasis. In a similar manner to observations from G. mellonella models, survival rates in mice post-infection with C. auris are strain-dependent [34,36,68,69], further affirming that genetic variability among the strains collected from diverse geographic locations impacts the organisms virulence. Two comparative virulence studies for multiple Candida species used an immunocompromised murine model to show that two C. auris isolates from India, and one isolate from Israel, displayed similar virulence to C. albicans strains [34,68].…”
Section: In Vivo Models Of Invasive Candidiasis To Study Host-c Aurisupporting
confidence: 73%
See 1 more Smart Citation
“…Recent studies have documented the virulence of C. auris in murine models of invasive candidiasis. In a similar manner to observations from G. mellonella models, survival rates in mice post-infection with C. auris are strain-dependent [34,36,68,69], further affirming that genetic variability among the strains collected from diverse geographic locations impacts the organisms virulence. Two comparative virulence studies for multiple Candida species used an immunocompromised murine model to show that two C. auris isolates from India, and one isolate from Israel, displayed similar virulence to C. albicans strains [34,68].…”
Section: In Vivo Models Of Invasive Candidiasis To Study Host-c Aurisupporting
confidence: 73%
“…Many fungal pathogens including C. auris disproportionally affect immunocompromised patients within healthcare settings and as such it is important to characterise host-pathogen interactions in models that mimic real-life circumstances. In a study by Xin et al (2019) it was shown that immunocompromised mice were slightly more susceptible to C. auris infection than immunocompetent mice [69], suggesting a crucial role for a healthy immune system in controlling C. auris virulence. A fascinating observation from histopathological analyses in these candidiasis murine studies was that C. auris accumulated in the kidney of the mice in the form of aggregates [34,39,68], potentially offering an explanation for the survival and persistence of the organism in vivo.…”
Section: In Vivo Models Of Invasive Candidiasis To Study Host-c Aurimentioning
confidence: 99%
“…From this, it could be suggested that under normal immunological conditions, the organism is non-invasive, and any immune response from the host is minimal. These postulations have been confirmed elsewhere, whereby immunocompetent mice were more resistant to C. auris infection than immunocompromised mice [15]. Such findings have been seen in humans; invasive C. auris infections generally occur in critically ill patients with serious underlying medical conditions resulting in haematological deficiencies and/or immunosuppression [5961].…”
Section: Discussionsupporting
confidence: 58%
“…Limited evidence also exists for studies investigating the interactions of C. auris with components of the host, although several in vivo models have been employed to document the virulence of C. auris . Of these, Galleria mellonella larvae infection models and murine models of invasive candidiasis have shown varying survival rates post-infection with C. auris [6, 8, 10, 1215], reaffirming that genetic variability amongst clades impacts the organisms virulence. However, such studies have been limited in investigating the host immune response to the organism.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to bacterial endophthalmitis, we observed that BALB/c mice are more susceptible to fungal (candida) endophthalmitis in comparison to B6 mice. Although there are no studies available testing the susceptibility of mouse strains to ocular fungal infections, Xin et al 75 evaluated the susceptibility of A/J, BALB/c and B6 mice to systemic Candida infection. In this study, systemic (intravenous) inoculation of 5 × 10 5 CFU of CA resulted in the death of BALB/c mice within one to two weeks, whereas the B6 mice survived for two to three weeks, even with a higher infective dose of 1 × 10 6 CFU.…”
Section: Discussionmentioning
confidence: 99%